Effects Of Cryofrequency on Localized Adiposity in Flanks - Silva, Rodrigo Marcel Valentim da; Silva, Manoelly Wesleyana Tavares da; Medeiros, Sâmela Fernandes de; Guerra, Sywdixianny Silva de Brito; Nobre, Regina da Silva; Meyer, Patricia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Cryofrequency is a characteristic used in clinical practice to reduce localized and flaccid adiposity, and promotes heat in our tissues by maintaining a surface. Objective: To investigate the effects of Cryofrequency in the reduction of adiposity located on the flank region. Methods: This is an experimental study, consisting of 30 female volunteers between 20 and 40 years old with flank fat. The applications were performed once a week, totaling eight applications, using the Andrus Criofrequência  - ADOXY MEDICAL, with parameters of 350 w of power, monopolar mode on the region of right and left flanks, with an area of 10 cm in height and 20 cm in width, for 8 minutes per area. The evaluations were performed before and after 4 and 8 Cryofrequency applications. Results: There was a reduction of the adiposity located in the flank region, with a significant decrease in the values of perimetry, plicometry and ultrasonography, and positive results in the questionnaire evaluating satisfaction and criofrequence reactions. Conclusion: Cryofrequency was effective for the treatment of localized adiposity, generating a positive satisfaction among the evaluated volunteers.